Impact of the Covid-19 Pandemic on The Financial Stability of The Insurance Sector in Poland - Anna SZKARLAT-KOSZALKA (Communications of International Proceedings, 2021)
The article analyzes and assesses the impact of the Covid 19 pandemic on the financial stability of the insurance sector. From an economic point of view, the Covid pandemic is viewed as a global shock, affecting all areas of economic life, including financial sector. It belongs to those sectors of the economy, which, due to their nature and interrelations, are particularly vulnerable to disruptions to processes caused by this shock. One of such areas is undoubtedly the financial system and its institutions, including insurance companies. The analysis carried out in the article is based on the official data published by the National Bank of Poland in the form of cyclical reports on the financial stability of the financial sector. The paper uses measures describing the financial situation of the insurance sector and affecting its solvency. Therefore, the adequacy of technical provisions was discussed, the insurer's investment was assessed qualitatively and quantitatively, as well as statutory solvency standards, i.e. the solvency capital requirement (SCR), the minimum capital requirement (MCR). It has been proven that the insurance sector, despite being part of the financial system, is less susceptible to the risk of financial stability loss than is the case for banks, and the main area of activity that may generate the risk of financial stability loss during the Covid pandemic -19 is the investment activity of insurers. The key aspect resulting from the essence of insurance and influencing financial stability is, above all, maintaining the trust of the insured.
Keywords: Financial Stability; Financial Institutions; Insurance Sector; Insurance Sector Investments Solvency Of Insurers